1962
DOI: 10.1055/s-0028-1100268
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen Über Die Inhaltsstoffe Der Blätter Von Combretum Micranthum G. Don

Abstract: Zu der Familie der Combretaceen, von der es allein in Afrika mehr als 250 Arten gibt, gehört der im westafrikanischen Küstengebiet (Sierra Leone, Guinea, Senegal usw.) heimische Strauch Combretum micranthum G. D o n (= Combretum Raimbaultii H e C k e 1 = Combretum altum G U i 11. et P e r r.), dessen Blätter unter der Bezeichnung ,KinkelibaU von den verschiedenen Eingeborenenstämmen als Heilmittel sehr geschätzt werden. Die Kenntnis der Droge und ihrer Anwendung, insbesondere in Form einer Abkochung der frisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Flavonoids are the major components of C. micranthum. Thirtyfour flavonoids belonging to the structural groups of isoflavonoids (1), anthocyanins (2)(3)(4), flavans (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), flavonols (17)(18)(19)(20)(21)(22)(23), flavones (24)(25)(26)(27)(28)(29)(30)(31)(32), flavononols (33) and flavonol polymers (34) were identified from the leaves and roots of C. micranthum.…”
Section: Flavonoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flavonoids are the major components of C. micranthum. Thirtyfour flavonoids belonging to the structural groups of isoflavonoids (1), anthocyanins (2)(3)(4), flavans (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), flavonols (17)(18)(19)(20)(21)(22)(23), flavones (24)(25)(26)(27)(28)(29)(30)(31)(32), flavononols (33) and flavonol polymers (34) were identified from the leaves and roots of C. micranthum.…”
Section: Flavonoidsmentioning
confidence: 99%
“…[26] He worked with the fresh leaf extract and identified a catechin and a tannin but, due to lack of equipment, he could not be specified. Twenty years later, Jentzsch et al (1962) studied dried leaves by thin layer chromatography (TLC) and identified two C-glycosylflavones, vitexin (25) and isovitexin (26). [33] With the advancement of technology (LC-MS and NMR), several flavonoids have been identified.…”
Section: Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isomeric flavonoids vitexin and saponaretin have been shown to be present in the leaves. 458 The leaves also contain the alkaloids combretacins. 459 The stem bark has been shown to yield similar alkaloids.…”
Section: Cola Acuminatamentioning
confidence: 99%